Parameter estimation in stock assessment modelling: caveats with gradient-based algorithms - Subbey, Sam (ICES journal of marine science, 2018)
Abstract Using simple illustrative examples, this note highlights some of the caveats with gradient-based algorithms. This class of algorithms underpins the state-of-the-art modelling platform in fisheries science. The goal is to sound a cautionary note about an increasing trend in fisheries science, where blind faith is being invested in results obtained from algorithms that are fast, and proven to have machine precision.